Fetal Stem Cells in Regenerative Medicine Principles and Translational Strategies - Fauza, Dario O.; Bani, Mahmud; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2016)
This book explores the regenerative properties of fetal stem cells, from feto-maternal cell traffic through perinatal stem cells, with a discussion of key topics including stem cell banking, drug screening, in utero stem cell transplantation and ethical considerations. The expertly authored chapters also delve into embryonic, amniotic membrane, and umbilical cord blood stem cells; fetal development models; fetal cell reprogramming; culture methods; disease models; perinatal gene therapy, and more. These chapters are grouped into four sections, each discussing a separate prenatal stem cell population and providing fascinating historical contexts for our knowledge of these systems. Featuring a foreword written by the renowned Dr. Joseph Vacanti of the Harvard Stem Cell Institute, Fetal Stem Cells in Regenerative Medicine: Principles and Translational Strategies is a welcome and timely contribution to the Stem Cell Biology and Regenerative Medicine series. It is essential reading for scientists and researchers, clinicians and residents, and advanced students involved in stem cells, regenerative medicine, tissue engineering, and related disciplines such as embryology.
1 Historical Perspectives -- 2 Feto-Maternal Cell Traffic and Labor -- 3 Paracrine Effects of Fetal Stem Cells -- 4 Immunogenicity and Immunomodulation of Fetal Stem Cells -- 5 Embryonic Stem Cells and Fetal Development Models -- 6 Fetal Cell Reprogramming -- 7 Historical Perspectives -- 8 Amniotic Membrane Stem Cell Populations -- 9 Amniotic Fluid Stem Cell Populations -- 10 Amniotic Fluid Stem Cell Culture Methods -- 11 MicroRNA expression in Amniotic Fluid Cells -- 12 Historical Perspectives -- 13 Umbilical Cord Blood Stem Cell Populations -- 14 Wharton$1 (Bs Jelly Stem Cells -- 15 Placental Stem Cells and Culture Methods -- 16 Fetal Stem Cell Banking -- 17 In Utero Stem Cell Transplantation -- 18 Fetal Tissue Engineering -- 19 Perinatal Gene Therapy -- 20 Transamniotic Stem Cell Therapy (TRASCET) -- 21 Stem Cells and Commercialization. .s
Keywords: Life sciences; Stem cells; Cell culture; Regenerative medicine; Tissue engineering; Embryology; Life Sciences; Stem Cells; Regenerative Medicine/Tissue Engineering; Cell Culture; Embryology; Electronic books